Transformasi Pembelajaran Biologi: Video Animasi Berbasis Masalah pada Materi Sistem Gerak Manusia - Puspita Sari, Anggun; Mellisa (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Biology learning on the topic of the human movement system often encounters challenges, particularly the lack of instructional media capable of clearly visualizing concepts. As a result, students struggle to understand scientific terminology, physiological processes, and inter-organ relationships. To address this issue, an animated video-based learning media integrated with Problem Based Learning (PBL) was developed with the aim of enhancing students’ understanding and engagement. This study aims to determine the validity and students’ responses toward the PBL-based animated video on the human movement system for grade XI. The research employed a Research and Development (R&D) method using the ADDIE model up to the development stage. Research instruments included interviews, needs questionnaires, observation sheets, expert validation sheets, and student response questionnaires. Samples were selected using Simple Random Sampling. The validation results showed that the media was categorized as very valid by material experts (92%), media experts (92%), and instructional experts (94%). Students’ responses reached 86%, categorized as good. This study contributes to knowledge development by providing an alternative biology learning media that integrates digital animation with the PBL approach, while also enriching studies on technology integration in science education.